Butyrate and Dietary Soluble Fiber Improve Neuroinflammation Associated With Aging in Mice - Matt, Stephanie M.; Allen, Jacob M.; Lawson, Marcus A.; Mailing, Lucy J.; Woods, Jeffrey A.; Johnson, Rodney W. (Frontiers in Immunology, 2018)
Aging results in chronic systemic inflammation that can alter neuroinflammation of the brain. Specifically, microglia shift to a pro-inflammatory phenotype predisposing them to hyper-activation upon stimulation by peripheral immune signals. It is proposed that certain nutrients can delay brain aging by preventing or reversing microglial hyperactivation. Butyrate, a short-chain fatty acid (SCFA) produced primarily by bacterial fermentation of fiber in the colon, has been extensively studied pharmacologically as a histone deacetylase (HDAC) inhibitor, and serves as an attractive therapeutic candidate, as butyrate has also been shown to be anti-inflammatory and improve memory in animal models. In the present study, we demonstrate that butyrate can attenuate pro-inflammatory cytokine expression in microglia in aged mice. It is still not fully understood however, if an increase in butyrate-producing bacteria in the gut as a consequence of a diet high in soluble fiber could affect microglial activation during aging. Adult and aged mice were fed either a 1% cellulose (low fiber) or 5% inulin (high fiber) diet for 4 weeks. Findings indicate that mice fed inulin had an altered gut microbiome and increased butyrate, acetate, and total SCFA production. In addition, histological scoring of the distal colon demonstrated that aged animals on the low fiber diet had increased inflammatory infiltrate that was significantly reduced in animals consuming the high fiber diet. Further, gene expression of inflammatory markers, epigenetic regulators, and the microglial sensory apparatus (i.e. the sensome) were altered by both diet and age, with aged animals exhibiting a more anti-inflammatory microglial profile on the high fiber diet. Taken together, high fiber supplementation in aging is a non-invasive strategy to increase butyrate levels, and these data suggest that an increase in butyrate through added soluble fiber such as inulin could counterbalance the age-related microbiota dysbiosis, potentially leading to neurological benefits.